A fabrication of a low-power low-noise neural recording amplifier based on flipped voltage follower. (July 2020) - Farouk, Tamer; Dessouky, Mohamed; Elkhatib, Mohamed
Abstract: In this work, a fabrication of low-voltage low-power and low-noise neural recording amplifiers are presented. An operational transconductance amplifier (OTA) was built using the flipped voltage follower (FVF). The low noise operation is achieved without increasing the bias current of the input transistors or decreasing the aspect ratio of the output transistors, which leads to large overdrive voltage. This proposed OTA is used to build a biopotential amplifier using AC coupling technique to achieve one of the lowest noise efficiency factor (NEF) of 2.13. This bioamplifier is fabricated using UMC 130 ​nm CMOS process and the measurement results are obtained. The proposed OTA is also used to design a second biopotential amplifier using active low-frequency suppression technique to achieve one of the lowest occupied area of 0.047 ​mm 2 while maintaining a reasonable Noise efficiency factor (NEF) of 4.27. The active low-frequency suppression technique is used to reject the DC offset voltage while preserving high input impedance and small area. The first bioamplifier consumes 2.2 ​μA from 1 ​V supply voltage. The input-referred noise is 3.7 μVrms . The bandwidth (BW) ranges from 25 ​Hz to 9.9 ​kHz. The achieved noise efficiency factor (NEF) is 2.13. The dynamic range is 55 ​dB. It occupies a silicon area of 0.112 ​mm 2 . The second bioamplifier consumes 5.2 ​μW from 1 ​V supply voltage. The input-referred noise is 4.7 μVrms. The BW ranges from 110 ​Hz to 9.7 ​kHz. The achieved NEF is 4.27. It occupies an area of 0.047 ​mm 2 .